Optimization Of Copper Via Filling Process For Flexible Printed Circuit Using Response Surface Methodology - Liew, Pay Jun; Wong, Kah Yan; Lau, Kok Tee; Jingsi, Wang (Penerbit UTeM, 2020)
Copper filling is a method for 3D stacked packaging and has been widely used in the semiconductor industry. However, as the downsizing of devices becomes an unavoidable trend, the tolerance of flexible printed circuit (FPC) fabrication has to decrease, resulting in high failure rates. To solve this problem, optimal process variables for copper filling must be studied to avoid the risk of failure. In this study, the effects of copper via filling parameters (current density (Id), fluid flow rate (Q) and filling time (tf)) on the filling behavior of a micro via (surface thickness, dimple depth and viafilling ratio) were investigated. The via on the FPC board was drilled using a laser drill with a dimension of 100 µm. Then, the FPC was immersed in an electrolyte for the copper via filling process. Experimental results showed that current density was significant to surface thickness, whereas fluid flow rate was significant to the dimple depth and via filling ratio. The optimum parameters to achieve thin surface thickness, low dimple depth and high via filling ratio were found to be at 1.5 A/dm2 of current density, 35 m3 /h of fluid flow rate and 60 min of filling time